Enhanced etching resolution of self-assembled PS-b-PMMA block copolymer films by ionic liquid additives. (6th March 2023) - Hao, Hongbo; Chen, Shuangjun; Ren, Jiaxing; Chen, Xuanxuan; Nealey, Paul
Abstract: Polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) is one of the most widely studied block copolymers for direct self-assembly because of its excellent compatibility with traditional processes. However, pattern transfer of PS-b-PMMA block copolymers (BCPs) remains a great challenge for its applications due to the insufficient etching resolution. In this study, the effect of ionic liquid 1-hexyl-3-methylimidazolium hexafluorophosphate (HMHF) additives on the line edge roughness (LER) performances of PS-b-PMMA self-assembled patterns was studied. Trace addition of HMHF kept the photolithography compatibility of PS-b-PMMA block copolymer films, but obviously increased their Flory–Huggins interaction parameter ( χ ) and enabled phase separation of disordered low molecular weight BCPs. LER value was effectively decreased by blending HMHF directly with PS-b-PMMA or from a supplying top layer of polyvinylpyrrolidone containing HMHF additives. This study shows an excellent strategy to improve the deficiencies of existing block copolymers.